A new look towards the determination of parameters of Heine and Abarenkov model potential using only vacancy formation energy in fcc crystals - Ghorai, Amitava (Diffusion Fundamentals, 2022)
The Heine and Abarenkov model potential (HAP) parameters (rc, A) have been calculated in this paper for twenty face-centered cubic (fcc) closed pack crystals. From the minimization of the structure dependent energy of the pure crystal the inter-relation between the two parameters of HAP has been initially determined. The calculation uses pseudopotential technique with nine different exchange correlation functions (ECF), either the available experimental value of the vacancy formation energy (EF1v) or that obtained from an empirical relation based on other experimental parameters (melting temperature, cohesive energy or activation energy) as tool. The variation of EF1v with the parameter A of HAP and ECF shows a sharp fall in EF1v near a very small value of A after which it shows constancy for all fcc crystals, and the parameters (rc, A) are determined near the bend. Comparison is made with other calculations and parameters of the Ashcroft model also. For increase in valency the parameter A of HAP increases and shows distinctly different curves.